Development of the surroundings of public schools in interwar period on the example of the Lublin region - Przesmycka, Elżbieta; Miłkowska, Ewa (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2016)
In the interwar period, many school assumptions arose. Most of them were characterized by care for the development of their surroundings. The authors present, on a few examples, the rules for the development of lands near schools on the example of implementation in the Lubelszczyzna region. Most of the planned environments of schools no longer exist or are very changed, which often negatively affects the native landscape of many places in Poland.